Peningkatan Produksi dan Analisis Kelayakan Usaha Padi Sawah Dengan Sistem Pengelolaan Tanaman Terpadu (PTT) - Ince Raden; Thamrin Thamrin; Eka Rahmawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2012)
This study aims to determine the growth and productivity of low land rice, Inpari 14 variety managed under the integrated farming system (PTT) and to conduct its feasibility analysis with the same system.  The research used Randomized Block Design (RBD) non factorial consisting of 9 treatments and 3 replications.  The treatments used, namely: control (“square” style of plant spacing 20cm x 20cm, transplanting 17 days after sowing, 3 seedlings per planting hole, and no manure); PTT 1 (square plant spacing 20cm x 20cm, transplanting 15 days after sowing, one seedling per planting hole, and 1 t ha-1 manure); PTT 2 (“legowo style” of plant spacing of 2:1, transplanting 15 days after sowing, planting one seedling per planting hole, and 1 t ha-1 manure); PTT 3 (square plant spacing of 20cm x 20cm, transplanting 15 days after sowing, 2 seedlings, and 1 t ha-1 manure); PTT 4 (legowo spacing of 2:1, transplanting 15 days after sowing, planting 2 seeds per planting hole, and 1 t ha-1 manure); PTT 5 (square planting spacing of 20cm x 20cm, transplanting 15 days after sowing, planting one seed per planting hole , and 2 t ha-1 manure); PTT 6 (legowo spacing 2:1, transplanting 15 days after sowing, planting one seed per planting hole, and 2 t ha-1 manure); PTT 7 (square planting spacing of 20cm x 20cm, transplanting 15 days after sowing, 2 seeds per planting hole, and 2 t ha-1 manure), and PTT 8 (legowo spacing of 2:1, transplanting 15 days after sowing, 2 seeds per planting hole, and 2 t ha-1 manure).  Results showed that an increase in production of 0.9 t ha-1 or 17.33 percent of the rice attained by PTT 8 treatment compared to the control with each production 5.25 t ha-1 and 4.34 t ha-1.  There were trends that the dried husk rice results ha-1 of legowo cropping systems, namely PTT 2 (4.96 t ha-1), PTT 4 (5.21 t ha-1) , PTT 6 (4.13 t ha-1), and PTT 8 (5.25 t ha-1) had a higher yield than the PTT tile systems treatment, namely PTT 1 (3.18 t ha-1); PTT3 ( 4.13 t ha-1); PTT 5 (4.17 t ha-1), and PTT 7 (4.19 t ha-1).  The PTT 8 treatment gave profit per hectare of Rp. 16,171,057 (Sixteen Million One Hundred Seventy One Thousand Fifty Seven Rupiah) that was higher compared to control of Rp. 13,002,557 (Thirteen Million Two Thousand Five Hundred Fifty Seven Rupiah)                                          that mean the PTT 8 treatment provided increased revenue by 20%